Persia : - Bradley-Birt, F. B. (J. B. Millet Co., 1910)
This book introduce about up the persian gulf, in bushire, beginning of the road, a night in a Persian hut, the pass of the old woman, by the graves of Sadi and Hafiz, the pass of God is great...